The impacts of company characteristics on corporate cash holdings: An empirical investigation of US firms. - SHI, TENGFEI (2017)
The corporate liquidity has attracted extensive attentions in the financial field. This empirical research investigates the determinants that influence the corporate cash holdings, the sample selection is all US firms for the period from 2004 to 2014. Three research models are applied in this research, which are OLS model, fixed effect model and SGMM model; the OLS model provides a general view of the determinants of cash holding, then the fixed effect model represents more detailed results as some other firm characteristics are added. The final results are mostly consistent with previous studies and theories, which suggests that cash flow is positively related with the cash retention, this implies the firms are willing to save more cash from the cash flow. Furthermore, firm size, leverage and non-cash liquidity are negatively correlated with the corporate cash holdings. In the end, the SGMM model is employed to ensure the empirical result is accurate.